The Impact of Storage on Phthalic Acid Esters Concentrations in Yogurts Packed in Plastic Cups - Jandlová, Marcela; Kumbár, Vojtěch; Jarošová, Alžbeta; Stará, Markéta; Pytel, Roman; Nedomová, Šárka; Ondrušíková, Sylvie (Mendelova univerzita v Brně, 2019)
Phthalic acid esters are used as plastic softeners and also can be found in food packaging materials. European legislation defines specific migration limits of plastic additives for plastic materials that come into contact with food. This study monitors the phthalic acid ester concentrations in yogurts after manufacturing and then after a 3-week storage. The studied yoghurts were natural yogurt with 1 % of chia flour, natural yogurt with 5 % of chia flour, natural yogurt with 1 % of bamboo fibre, natural yogurt with 5 % of bamboo fibre and natural yogurt. The analysed phthalic acid esters were dibutyl phthalate (DBP) and di-(2-ethylhexyl) phthalate (DEHP). The average phthalate concentrations in plastic cups were detected for DBP of 59.5 µg/g and for DEHP of 9.0 µg/g of the plastic material. Higher DBP concentrations than DEHP concentrations were also found in all studied yogurts. The average DBP concentrations in yogurts were detected from 1.8 µg/g up to 5.0 µg/g of the original matter and the average DEHP concentrations were determined from 0.5 µg/g up to 1.0 µg/g of the original matter. No statistically significant difference was found when comparing phthalic acid ester concentrations in yogurts immediately after production and after three weeks of storage. However, in our study in all cases of yogurts, the DBP concentrations were higher than the specific migration limit set by the legislation (0.3 mg/kg) and the DEHP concentrations were in all cases of yogurts lower than the specific migration limit set by the legislation (1.5 mg/kg).
Keywords: Contaminant; DBP; DEHP; Dietary fibre; During storage; Migration; Yogurt